2004
DOI: 10.1080/15287390490492449
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION AND IDENTIFICATION OFLegionellaSPECIES FROM GROUNDWATERS

Abstract: Legionellae are opportunistic bacterial pathogens causing Legionnaires' disease and Pontiac fever and are ubiquitous in surface waters and in infrastructure to contain or distribute water, including pipes, cooling towers, and whirlpool spas. Infection in community-acquired and nosocomial outbreaks is by exposure to contaminated aerosols. Little is known about the presence of legionellae in groundwater. This study used samples from various locations in the United States and Canada to determine if legionellae co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
2
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 30 publications
1
35
2
8
Order By: Relevance
“…The available evidence is consistent with this second hypothesis, although bacterial competition may have played a role in the emergence of more resistant L. pneumophila. (i) L. pneumophila is often found with Legionella species other than L. pneumophila in water (5,8,9,17,25). (ii) An outbreak of Legionnaires' disease caused by L. pneumophila, despite the identification of only L. anisa in tap water, was reported in a previous study (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available evidence is consistent with this second hypothesis, although bacterial competition may have played a role in the emergence of more resistant L. pneumophila. (i) L. pneumophila is often found with Legionella species other than L. pneumophila in water (5,8,9,17,25). (ii) An outbreak of Legionnaires' disease caused by L. pneumophila, despite the identification of only L. anisa in tap water, was reported in a previous study (26).…”
Section: Discussionmentioning
confidence: 99%
“…Legionella species are ubiquitous in many water systems (6,8,9,17,22,27)-including hospital water systems (30,31,39)-with Legionella pneumophila and Legionella species other than L. pneumophila isolated together (3,11) or alone (19,37). The most frequent species are L. pneumophila and L. anisa (5,12,16,18,36).…”
mentioning
confidence: 99%
“…Faecal bacteria may also occur in pristine ground and surface waters that are not impacted by human activity; they can be attributed to wild animals (Niemi and Niemi 1991). Recent research revealed that small numbers of microbial pathogens, such as Legionella, might be detectable in pristine waters without any discernible contamination source, and without the presence of faecal indicator bacteria (Brooks et al 2004;Schaffter et al 2004). In some cases, microbial pathogens thus seem to be part of the "natural" biocenosis in groundwater.…”
Section: Bioindicators For Groundwater Qualitymentioning
confidence: 99%
“…L. pneumophila has been detected only sporadically by use of the cultivation method in untreated groundwater (GW) and in treated water at temperatures below 20°C (4,14,20,24,56). However, cultivation-independent techniques, including immunological methods, fluorescent in situ hybridization (FISH), and PCR-based methods, clearly revealed the common presence of Legionella species in aquatic environments, even at temperatures below 20°C (11,12,14,44,50). In addition, FISH methods showed that undefined Legionella species may represent up to 7% of biofilms grown in treated water (52).…”
mentioning
confidence: 99%